Pengaruh Kompetensi, Kompensasi dan Kepemimpinan Terhadap Kinerja Karyawan - Samsul Arifin; Arif Rachman Putra; Cahya Fajar Budi Hartanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Successful companies get contributions from the performance of their employees. Employees are the most important and foremost asset in a company. With good and quality employee performance, this will help the company to achieve its goals. Three things affect employee performance, namely competence, compensation and leadership. Competence is the main requirement to do work assignments. Compensation is the level of benefits received by employees. Excellent leadership quality to lead a company, by finding employees who are competent in the field of work that has been determined and provide adequate compensation in stages for employees who excel, this will improve the performance of company employees. The technique used in determining the sample is purposive sampling. The number of samples used was 35 people from the total population. The results showed that, [1] competence had a significant effect on job performance; [2] compensation has a significant effect on job performance; [3] leadership has a significant effect on job performance